The Association between Self-Rated Health Status and Increasing Age among Older Japanese Living in a Rural Community over a 6-Year Period: A Longitudinal Data Analysis - Ishizaki, Tatsuro; Yoshida, Hideyo; Suzuki, Takao; Shibata, Hiroshi (Gerontology (Basel), 2009)
Background: Although previous longitudinal studies reported that changes in self-rated health (SRH) status were not explained by aging of population, they do not adequately adjust for potential confounding factors of SRH status. Objective: It was the aim of our study to examine the association of SRH status with increasing age among older individuals in a Japanese community during a 6-year period, 1994 through 2000. Methods: We conducted a community-based prospective cohort study. Subjects were a total of 710 men and women, ranging in age from 67 to 91 years at the beginning of the 1994 survey. Independent variables potentially associated with SRH were obtained from interview surveys conducted in 1994, 1996, 1998 and 2000. The dependent variable was SRH status obtained at each survey. Results: Univariate analysis showed no significant trends in the proportions of subjects with good SRH over time. However, analyses using the generalized estimating equations methodology revealed that aging was significantly associated with a small increase in the proportion of participants with good SRH, after adjusting for potential confounders. The analysis also revealed that factors contributing to good SRH included independence in activities of daily living and instrumental activities of daily living, as well as absence of the following: recent hospitalization history, chronic medical conditions, current complaints of pain and depressive symptomatology. Conclusion: This study demonstrated that after adjusting for negative confounders, aging was independently associated with a small but significant increase in the proportion of older individuals with good SRH.